Vývoj tržieb a zisku vo vybraných spoločnostiach pôsobiacich v sektore rozhlasového vysielania - Čerňanová, Lucia, 1997-
Through This Article, We Want to Point out the Topic of the Creative and Cultural Industry, Focusing on the Analysis of the Development of Sales and Profit in the Radio Broacasting Sector.